American Patriots : The Story of Blacks in the Military from the Revolution to Desert Storm - Bolden, Tonya; Buckley, Gail Lumet (New York : Crown Publishers, 2003)
Presents the story of the Black experience in United States military history.
Includes bibliographical references (p. 221-224) and index.
Keywords: African American soldiers -- Biography; African American soldiers -- Juvenile literature. -- History; African American soldiers; Race relations; United States -- Juvenile literature. -- History, Military; United States -- Juvenile literature. -- Armed Forces; United States -- Juvenile literature. -- Race relations; United States -- History, Military